Susceptibility of Aedes aegypti larvae in East Java towards commercial Temephos at different doses - Khaleyla, Firas; Rohmah, Etik Ainun; Mulyatno, Kris Cahyo (Jurnal Biologi Udayana, 2021)
Control of Ae. Aegypti population is performed as an effort to suppress the transmission of dengue virus, one of the methods is sprinkling of temephos larvicide. Operational dose of temephos used in Indonesia (1 mg/L) is higher from recommended dose of WHO (0.012 mg/L). In East Java, commercial temephos are found to have different application doses of 8 g/L (8G) and 10 g/L (10 G). This study was designed to know the susceptibility of Ae. aegypti population from Jember (JEM), Surabaya (SBY), and Entomology Laboratory of Universitas Airlangga collection (LAB) towards temephos 8G and 10G starting at high (1 mg/L) to low concentrations(0.015625 mg/L). Larvae mortality test was performed based on WHO standard method with 4 times replication. Data was analyzed statistically. Results showed that the three groups of Ae. aegypti larvae had mortality level at >90% in the lowest concentration applied (0.015625 mg/L) at time threshold of 240 minutes, for both temephos8 G and 10 G. Significant difference of larvae mortality towards highest (1 mg/L) and lowest dose (0.015625 mg/L) was found in JEM, at both 8 G and 10 G doses, and LAB at 8 G dose. JEM and SBY groups were found to have resistance ratio 95 (RR 95 ) to temephosat low category (<5) compared to LAB. All groupstill retained susceptibility towards commercial temephos larvicide at low dose (0.015625 mg/L). Based on results, we recommendedlowering the operational dose of larvicide temephos used for population control of Ae. aegypti vector population in East Java.